2006
DOI: 10.1002/jca.20087
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis in children with graft‐versus‐host disease

Abstract: Acute and chronic graft-versus-host disease (GVHD) are major complications after allogeneic hematopoietic stem cell transplantation. Systemic corticosteroid is the first line of therapy but only half of the patients will respond. The management of steroid-refractory or steroid-dependent GVHD is challenging. Intensification of immunosuppression has been the main strategy but the response rate is not satisfactory. Furthermore, the incidence of treatment-related toxicity and opportunistic infection is unacceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This is in accordance to earlier published reports by others. [5][6][7][8][9][10][11][12] Most patients had not had adverse effects. Fungal infections developed in patients who were on treatment with high-dose steroids, probably the main cause of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance to earlier published reports by others. [5][6][7][8][9][10][11][12] Most patients had not had adverse effects. Fungal infections developed in patients who were on treatment with high-dose steroids, probably the main cause of them.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, there are few published studies analyzing clinical outcome in pediatric patients undergoing ECP as steroidrefractory GVHD treatment. [7][8][9][10][11][12] This long-term follow-up study was designed to analyze clinical outcome in a group of pediatric patients who underwent ECP for treatment of steroid-refractory acute and chronic GVHD.…”
mentioning
confidence: 99%
“…Very recently, it has been reported that the proportion of immature CD19+CD21-B lymphocytes may be correlated with ECP response in cGVHD even though this is a report on a small number of patients. 13 In the pediatric setting, many authors report a response rate to ECP in steroid-resistant aGVHD ranging from 50% to 100% (depending on the organs involved) 3,[14][15][16] and in cGVHD from 33% to 93%. 10,16 In aGVHD steroid-resistant patients, the probability of survival at 4 years is significantly increased in complete responders to ECP (59%), while it decreases dramatically to 11% for nonresponders.…”
mentioning
confidence: 99%
“…13 In the pediatric setting, many authors report a response rate to ECP in steroid-resistant aGVHD ranging from 50% to 100% (depending on the organs involved) 3,[14][15][16] and in cGVHD from 33% to 93%. 10,16 In aGVHD steroid-resistant patients, the probability of survival at 4 years is significantly increased in complete responders to ECP (59%), while it decreases dramatically to 11% for nonresponders. 16 In cGVHD refractory patients, a significantly higher 5-year overall survival rate was observed in ECP responders compared to nonresponders (96% vs. 58%).…”
mentioning
confidence: 99%
“…Another approach is to put the mononuclear cell suspension in the UVAR XTS machine for processing (both two-step procedures). 32 Our group has been able to use the standard procedure with the UVAR Table 3 Approaches to post-HSCT GVHD prophylaxis and treatment in children XTS in children down to 20 kg. We follow an algorithm demanding a specific hematocrit before ECP, depending on the child's weight, and normal saline is given pre-ECP depending on expected extracorporeal volume.…”
mentioning
confidence: 99%